THE IMPACT OF FBFC-CI ON BEHAVIORAL SYMPTOMS ASSOCIATED WITH DEMENTIA AND PSYCHOTROPIC USAGE. (11th November 2018) - Vigne, E; Galik, E; Holmes, S D; Resnick, B
Abstract: Neuropsychiatric symptoms, such as delusions, hallucinations, depression, aggression, and agitation occur in two-thirds of nursing home residents with dementia. These behavioral symptoms are most likely to occur during personal care interactions and challenge and frustrate caregivers. Pharmacologic management of behavioral symptoms among residents with dementia has been minimally effective and is fraught with significant risks, such as, falls, fractures, delirium, parkinsonism, stroke, pneumonia, and death. FBFC-CI is a behavioral intervention focused on optimizing function and physical activity of residents with dementia during all care interactions. Residents in settings in which FBFC-CI was implemented had a decrease in resistiveness to care and a decrease in use of antipsychotics at four months post implementation of the intervention. There was no change in mood, agitation, use of antidepressants, anxiolytics or mood stabilizing medications. Importantly, there was no evidence that engaging residents with dementia in function and physical activity exacerbated behavioral symptoms.